2020
DOI: 10.1097/pas.0000000000001537
|View full text |Cite
|
Sign up to set email alerts
|

Specific Biomarker Expression Patterns in the Diagnosis of Residual and Recurrent Endometrial Precancers After Progestin Treatment

Abstract: Background: Conservative management with progestin is a treatment option for atypical hyperplasia (AH). However, pathologic diagnosis of residual/recurrent lesions is often problematic because of the profound morphologic changes induced by progestin and the lack of established diagnostic criteria for progestin-treated residual AH. Methods: We conducted a longitudinal study of 265 endometrial biopsies from 54 patients with a history of AH on progestin th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 30 publications
0
13
1
Order By: Relevance
“…Similarly, an association between PTEN protein expression and prognosis was not demonstrated in the EEC and AH groups before treatment. This was not consistent with the data previously reported by Chen et al ( 14 ). In a previous meta-analysis or systematic review of fertility-sparing treatment of EEC or AH in young women, no clear predictive biomarkers which were associated with remission, recurrence or progression could be identified following multivariate analysis ( 30 ).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Similarly, an association between PTEN protein expression and prognosis was not demonstrated in the EEC and AH groups before treatment. This was not consistent with the data previously reported by Chen et al ( 14 ). In a previous meta-analysis or systematic review of fertility-sparing treatment of EEC or AH in young women, no clear predictive biomarkers which were associated with remission, recurrence or progression could be identified following multivariate analysis ( 30 ).…”
Section: Discussioncontrasting
confidence: 97%
“…The patients underwent follow-up using endometrial sampling by hysteroscopy or curettage to assess endometrial changes every 3 months. According to Wheeler et al ( 13 ) and Chen et al ( 14 ), response to treatment based on the latest biopsy can be classified as follows: i) Complete response (CR), defined as a proliferative, secretory, inactive or atrophic endometrium without hyperplasia or atypia; ii) partial response (PR), defined as histological regression with decidual endometrial change; iii) stable disease (SD), defined as the persistence of EEC or AH/EIN in both the original and final specimens; iv) progressive disease (PD), defined as progression to lesions if the pre-treatment specimen showed AH whereas the latest specimen showed EEC, or if the original specimen showed grade 1 EEC whereas the latest specimen showed EEC grade 2 or 3; and v) recurrent disease (RD), defined as a CR to progestin treatment once or more according to a follow-up biopsy, but in which EEC/AH recurrence was subsequently identified. All pre-treatment and post-treatment evaluations were independently performed by two experienced gynecological pathologists.…”
Section: Methodsmentioning
confidence: 99%
“… 7 , 52 A large recent longitudinal investigation of Pax2 and Pten expression patterns in serial biopsies from women treated with progestin found that expression patterns in pretreatment AH/EIN were consistently recapitulated by AH/EIN present following treatment. 53 β-Catenin patterns are also likely to be recapitulated following treatment. 37 Thus, in addition to facilitating the initial diagnosis of AH/EIN, establishment of baseline expression patterns should be useful diagnostically in follow-up biopsies in the setting of progestin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation is across an entire biopsy, not limited to the most worrisome foci (making it useful even with limited samples), and it is able to detect aberrancy across a wide range of morphologic alterations as documented in this and prior studies. 27,54 At the same time, the 3-marker panel has some shortcomings. In addition to the time and cost associated with 3 immunostains, it too has nuances in interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Interpretation is across an entire biopsy, not limited to the most worrisome foci (making it useful even with limited samples), and it is able to detect aberrancy across a wide range of morphologic alterations as documented in this and prior studies. 27 , 54 …”
Section: Discussionmentioning
confidence: 99%